New techniques of malware detection using FTP Honeypot systems - Perevozchikov, Valentin A.; Shaymardanov, Timur A.; Chugunkov, Ilya V. (2017 IEEE Conference of Russian Young Researchers in Electrical and Electronic Engineering (EIConRus), 2017)
The paper deals with the increase of protection systems' efficiency by means of the Honeypot technology. The design principles of this technology are described. We propose several ways of the file storages effective organization. Plans of collecting statistical information on malefactor's actions are discussed. Also the efficiency of the suggested approach is estimated.